2020/2021 Philippine Human Development Report: Socioeconomic Mobility and Human Development - de Dios, Emmanuel (Archīum Ateneo, 2021)
This issue of the Philippine Human Development Report explores a new perspective on the advancement of living standards; one that not only documents achieved human development outcomes but that also inquires into the processes that allow people and families to improve their condition through time and sustain such improvements across generations. It views welfare changes not only through the usual dichotomy of poor and nonpoor but through a prism that recognizes the increasing social and economic differentiation of families and individuals in the country. The Report shows that Filipino households have been moving across different welfare trajectories over time and across generations. At least until the breakout of the COVID- 19 pandemic; the proportion of households who were extremely poor was declining while the nonpoor; composed of the vulnerable; the economically secure; and the upper middle class had increased. The global pandemic and its effects on the country have momentarily interrupted this trend and exposed the vulnerability of the improvements in the situation of socio-economic mobility. It has increased the probability of more frequent and abrupt swings in welfare in the future. But future research is only bound to show that people have adjusted to the crisis in better or worse ways; reflecting the pre-existing social heterogeneity. While upward and downward movements in income itself are nothing new; the emergence of increasingly distinct socio-economic classes poses new questions and challenges. The Report tries to identify the different factors that cause individuals and households to be promoted or relegated on the welfare ladder—these include both nonhuman wealth; such as land; physical property and financial assets; and human capital transfers; such as parents’ investments in their children’s education and health; as well as parental efforts in the formation of life skills and their influence on marriage matches and reproductive decisions. The Report tries to quantify empirically the effect of these various factors; using a specially constructed dataset; and from other studies. Differences in education and health status of families across classes affect the direction and degree of welfare change over time and across generations. The persistence of these inequalities creates unequal human capital development that puts households in lower classes at a disadvantage. It also shows how people belonging to the upper classes are afforded greater choice and are able harness networks to optimize the use of their human capital.Given changing social circumstances; however—particularly the gradual reduction of the statutorily poor to a minority in society—there is a greater need for integrated programs that explicitly envision the upward mobility of different categories of individuals and families over time and across generations. Such a strategy must recognize that different households confront different life obstacles and that there are different pathways for them to move up the socioeconomic ladder.The implication is that long-standing blanket policies targeting only the poor—especially in terms of subsistence—although still necessary; may no longer suffice. Policies are required that take into account the differentiated capacities and needs of households and individuals in the entire process of upward social mobility. As the Report notes; “government need not implement a single type of benefit scheme for these different categories—one size does not fit all.” This requires the government to design programs that are differentiated in both provision and financing depending on the socioeconomic groups they intend to benefit. While the extremely poor should continue to benefit from direct provision and transfers; this is less true for the middle classes; who may benefit more from mutual insurance or access to forms of credit. Governance structures and financing systems must move beyond the customary sectoral approach (e.g.; undifferentiated crop programs or blanket subsidies and discounts) and instead provide assistance that is differentiated according to the requirements of individuals and households. The intergenerational nature of mobility also implies more focus should be given to policies and programs that improve opportunities and secure the future of children of the poorest households.